MODELING A HYBRID FLOW SHOP PROBLEM APPLIED TO THE PRODUCTION LINE OF A HAIR COSMETICS FACTORY - Cunha,Carlos Henrique Furtado da (2020)
ABSTRACT Many industries have a complex manufacturing line, which complicates the planning of their productions. One possible solution to this problem is the optimization of the production line. In this work, mixed integer linear programming models are capable of representing the productive organization of the production line of a hair cosmetics factory, characterized by hybrid flow shop problem. The proposed models can be solved using CPLEX® Optimization Studio for real cases of the studied industrial production line. The objective was the minimization of the production makespan and the completion time. The innovation of this work is the application of the mixed integer linear programming method in complex cases, which are often found in industries and are solved by heuristic methods, simulations, or approximations of analytical methods.